1982
DOI: 10.1136/bmj.285.6345.843
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins and kwashiorkor: a study in Sudanese children.

Abstract: Blood and urine samples from 252 Sudanese children were investigated for their aflatoxin content by highperformance liquid chromatography. The children comprised 44 with kwashiorkor, 32 with marasmic kwashiorkor, 70 with marasmus, and 106 age-matched, normally nourished controls. Aflatoxins were detected more often and at higher concentrations in sera from children with kwashiorkor than in the other malnourished and control groups. Aflatoxicol, a metabolite of aflatoxins B, and B,, was detected in the sera of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(39 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…Aflatoxin intake is related to kwashiorkor [24] and Reye syndrome [25], and aflatoxins induce liver damage in undernourished individuals [26]. Aflatoxins are classified as Group I carcinogens in humans [27]; they are potent mutagens and teratogens, and they cause abortions, immunosuppression and cardiovascular symptoms.…”
Section: Mycotoxins That Affect the Human Cardiovascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Aflatoxin intake is related to kwashiorkor [24] and Reye syndrome [25], and aflatoxins induce liver damage in undernourished individuals [26]. Aflatoxins are classified as Group I carcinogens in humans [27]; they are potent mutagens and teratogens, and they cause abortions, immunosuppression and cardiovascular symptoms.…”
Section: Mycotoxins That Affect the Human Cardiovascular Systemmentioning
confidence: 99%
“…Aflatoxins are considered unavoidable toxins [22]. Biological control measures include lactic acid bacterial fermentation, which is known to render cereal-based foods and beverages safe [23], and the use of aluminosilicates, glucomannans and optimal storage conditions to prevent fungal growth.Aflatoxin intake is related to kwashiorkor [24] and Reye syndrome [25], and aflatoxins induce liver damage in undernourished individuals [26]. Aflatoxins are classified as Group I carcinogens in humans [27]; they are potent mutagens and teratogens, and they cause abortions, immunosuppression and cardiovascular symptoms.…”
mentioning
confidence: 99%
“…Studies in human populations consuming aflatoxincontaminated peanut butter revealed the presence of aflatoxin M1 in urine, as detected by TLC analysis (16), and aflatoxins were also found in the urine of Sudanese children suffering from kwashiorkor examined by HPLC analysis (17). Chemical screening methods for detection of aflatoxin and metabolites in human urine (18) and serum (19) have been reported.…”
Section: Strategies For Exposure Monitoringmentioning
confidence: 99%
“…AFs are some of the most potent toxic substances found in foods and feeds [1]. Numerous studies have also linked AFs to various diseases, such as cancer of the liver and hepatitis B and C. High levels of AF were detected in children with kwashiorkor in Sudan [2], in Durban, South Africa [3] and in Nigeria [4]. AFs are ubiquitous but are more commonly found in warm and humid climates and affect about one-quarter of the global food and feed crop output [5,6].…”
Section: Introductionmentioning
confidence: 99%